2014
DOI: 10.1177/194008291400700406
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Deforestation Affects the Structural Dynamics of Headwater Streams in Southern Brazilian Amazonia

Abstract: Comparative studies of streams with altered versus conserved riparian zones are important to evaluate the degree of alterations caused by inappropriate use of these streams' vital buffer zones. The aim of this study was to determine the impact of riparian deforestation on the habitat structure of southern Brazilian Amazonian headwater streams, as well as to provide elements for impact assessment and the monitoring of these water bodies. We selected ten sites and two headwater streams at each site; one stream w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 60 publications
(105 reference statements)
0
21
0
3
Order By: Relevance
“…HII may be recommended as part of those protocols, since it partly reveals effects of disturbance to the aquatic communities. HII remains an inexpensive measure of riparian zone structural variables such as canopy openness, litter bank volume, number of retention devices, proportion of benthic substrate components, and water temperature [54], and should be considered for monitoring riparian deforestation in Northern Brazil’s Cerrado river ecosystems. The HII is directly related to the degree of environmental conservation and has been successfully used in other studies to evaluate the integrity in aquatic systems [55,56,57,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HII may be recommended as part of those protocols, since it partly reveals effects of disturbance to the aquatic communities. HII remains an inexpensive measure of riparian zone structural variables such as canopy openness, litter bank volume, number of retention devices, proportion of benthic substrate components, and water temperature [54], and should be considered for monitoring riparian deforestation in Northern Brazil’s Cerrado river ecosystems. The HII is directly related to the degree of environmental conservation and has been successfully used in other studies to evaluate the integrity in aquatic systems [55,56,57,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Northern Cerrado rivers are similar to Amazonia rivers in that they vary throughout the rainfall and dry period cycle [60]. Bleich et al [54] found severe alterations in habitat structure (especially water temperature, oxygen, suspended materials, and nitrite concentrations) and availability of substrates (litter, trunks, and retention devices) in altered streams (measured by HII) in comparison to pristine ones. According to Pearson [61], current velocity is one of the main environmental correlates with species abundances and multivariate scores in tropical Australia.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Amazonian, deforestation of the riparian forest also led to the loss of variability in headwater stream habitat structure across hydrological periods (Bleich et al, 2014). -Delgado et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The increased autochthonous primary production in altered streams, that are poor in nutrients in the southern Amazon (Bleich et al, 2014), reflects the greater insolation in these environments, which were previously shaded by riparian forest (Fletcher et al, 2000). However, the lower amount of algae during flooding in the southern Amazon reflects the possibility that rains scour these organisms.…”
Section: Ruedamentioning
confidence: 98%
See 1 more Smart Citation